Anti-mold, self-cleaning superhydrophobic bamboo fiber/polypropylene composites with mechanical durability - Zhao, He; Lin, Xinxing; Lu, Shengchang; Wu, Hui; Zhou, Xiaxing; Huang, Liulian; Li, Jianguo; Shi, Jianping; Tong, Wenxuan; Yuan, Hongmei; Chen, Lihui (Frontiers in Chemistry, 2023)
Bamboo fiber/polypropylene composites (BPCs) have been widely used in buildings, interior decoration, and automobile components. However, pollutants and fungi can interact with the hydrophilic bamboo fibers on the surface of Bamboo fiber/polypropylene composites, degrading their appearance and mechanical properties. To improve their anti-fouling and anti-mildew properties, a superhydrophobic modified Bamboo fiber/polypropylene composite (BPC-TiO2-F) was fabricated by introducing titanium dioxide (TiO2) and poly(DOPAm-co-PFOEA) onto the surface of a Bamboo fiber/polypropylene composite. The morphology of BPC-TiO2-F was analyzed by XPS, FTIR, and SEM. The results showed that TiO2 particles covered on Bamboo fiber/polypropylene composite surface via complexation between phenolic hydroxyl groups and Ti atoms. Low-surface-energy fluorine-containing poly(DOPAm-co-PFOEA) was introduced onto the Bamboo fiber/polypropylene composite surface, forming a rough micro/nanostructure that endowed BPC-TiO2-F with superhydrophobicity (water contact angle = 151.0° ± 0.5°). The modified Bamboo fiber/polypropylene composite exhibited excellent self-cleaning properties, and a model contaminant, Fe3O4 powder, was rapidly removed from the surface by water drops. BPC-TiO2-F showed excellent anti-mold performance, and no mold was on its surface after 28 days. The superhydrophobic BPC-TiO2-F had good mechanical durability and could withstand sandpaper abrasion with a weight load of 50 g, finger wiping for 20 cycles, and tape adhesion abrasion for 40 cycles. BPC-TiO2-F showed good self-cleaning properties, mildew resistance, and mechanical resistance, giving it promising applications for automotive upholstery and building decoration.